2007
DOI: 10.1128/iai.00834-07
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Protective Efficacy of Intramuscular Vaccination with a LivearoADerivative ofPasteurella multocidaB:2 against Experimental Hemorrhagic Septicemia in Calves

Abstract: Three groups of five calves, namely, V1, V2, and V3, were immunized intramuscularly at 4 and 8 weeks of age with ca. 10 9 , 10 8 , and 10 7 CFU, respectively, of a derivative of Pasteurella multocida B:2 wild-type strain 85020 containing a deletion in the aroA gene (strain JRMT12). The first and second vaccinations resulted in significantly (P < 0.01) higher rectal temperature responses in groups V1 and V2 than in group V3. Serum immunoglobulin M (IgM) and IgG titers did not increase in any group until after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Systemic or intranasal vaccination of mice elicited solid immunity (Tabatabaei et al 2002 ). Unfortunately, in calves intramuscular injection of the vaccine was necessary to stimulate protective immunity, with intranasally vaccinated calves remaining completely susceptible (Hodgson et al 2005 ;Dagleish et al 2007 ).…”
Section: Live Vaccinesmentioning
confidence: 99%
“…Systemic or intranasal vaccination of mice elicited solid immunity (Tabatabaei et al 2002 ). Unfortunately, in calves intramuscular injection of the vaccine was necessary to stimulate protective immunity, with intranasally vaccinated calves remaining completely susceptible (Hodgson et al 2005 ;Dagleish et al 2007 ).…”
Section: Live Vaccinesmentioning
confidence: 99%
“…A live-attenuated vaccine for HS might be a better alternative vaccine as, by mimicking the ability of the pathogen to infect the host, but without causing disease, a more prolonged protective immune response may be induced. A live-attenuated vaccine developed by Tabatabaei et al [4], by mutating a housekeeping gene aroA , proved to be highly attenuated yet protective in mice and in cattle [4][6]. In later work, Othman et al [7] reported on the ability of the live vaccine strain to adhere to and to invade embryonic bovine lung (EBL) cells with an efficiency similar to the wild-type strain.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, 11 aroA , three aroC , and two aroD genes have been mutated and proven to be virmugens. Live attenuated vaccines have been generated by mutating aroA in 11 strains belonging to eight genus such as Bordetella [14], Pasteurella [15], Salmonella [16], Shigella [17], Staphylococcus [18], and Yersinia [19]. Except Gram-positive S. aureus , all other pathogens are Gram-negative.…”
Section: Resultsmentioning
confidence: 99%